Redesain Pengisian Kekosongan Jabatan Wakil Presiden Menurut Konstitusi - Susanto, Antono Adhi; Sujatnika, Ghunarsa (Media Iuris, 2024)
AbstractThe regulation of the period for filling the vacant position of Vice President as stipulated in Article 8 paragraph (2) of the 1945 Constitution of the Republic of Indonesia (Constitution) only governs the duration of People's Consultative Assembly (MPR) sessions. Nonetheless, it does not govern the appointment of the elected Vice President. Therefore, it left problems in the effectiveness and efficiency of electing the Vice President. This research focused on two issues, the practice of filling the Vice President's vacant position in Indonesia and its ideal concept in Indonesia. This research applies normative legal research method with a comparative approach to provisions related to the Vice President's vacant position in several countries. In the end, the conclusion shows two findings. First, after the amendment to the Constitution, a mechanism for filling the vacant position of Vice President has been regulated, supported by two factors, Vice President is a constitutional position, also because of the effectiveness and efficiency of the elections through the MPR. Second, Article 8 paragraph (2) of the Constitution needs to be revised by requiring one candidate, limiting the period for the Vice President's election to seven days, as well as amending MPR's authority to approve and fill the position of interim Vice President.  Keywords: Redesign; Filling Post; Vice President. AbstrakPengaturan jangka waktu pengisian kekosongan jabatan Wakil Presiden dalam Pasal 8 ayat (2) Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 hanya mengatur waktu sidang MPR dan bukan mengatur penetapan Wakil Presiden terpilih, sehingga masih terdapat permasalahan efektivitas dan efisiensi terpilihnya Wakil. Penelitian ini mengkaji dua hal, yaitu praktik pengisian kekosongan jabatan Wakil Presiden di Indonesia dan konsep ideal pengisian kekosongan jabatan wakil presiden di Indonesia. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan perbandingan pengaturan kekosongan jabatan Wakil Presiden pada konstitusi beberapa negara. Hasil penelitian menyimpulkan, Pertama, pasca amendemen UUD 1945 telah diatur mekanisme pengisian kekosongan jabatan Wakil Presiden karena Wakil Presiden merupakan jabatan konstitusional dan mempertimbangkan faktor efektivitas dan efisien dengan pemilihan melalui MPR. Kedua, Pasal 8 ayat (2) UUD 1945 perlu diperbaiki dengan mengatur satu orang calon, pembatasan waktu terpilihnya Wakil Presiden menjadi tujuh hari, perubahan peran MPR untuk melakukan persetujuan dan pengisian jabatan Wakil Presiden sementara.Kata Kunci: Redesain; Pengisian Jabatan; Wakil Presiden.